A kinetic study on the photodynamic properties of the xanthene dye merbromin (mercurochrome) and its aggregates with amino acids in aqueous solution - Martínez, Gabriela (1993)
The photophysical properties and the photobleaching of the xanthene dye merbromin(MR), as well as the production and quenching of singlet molecular oxygen, O₂(¹∆g), were investigated in aqueous solutions, in comparison with the xanthene dyes eosine (Eos) and rose bengal (RB). MR photobleaches in the absence of O₂ in a process involving the solvent (H₂O or alcohols). No participation of O₂ or O₂(¹∆g) could be established in the presence of O₂, although O₂ Is consumed. In aqueous and alcoholic solutions, MR forms ground state charge transfer (CT) complexes with biologically relevant electron donor amino acids, such as histidine, thyptophan, and other indolic derivatives. These complexes are formed with relatively high association constants (3 x 10³ - 5 x 10³) and are mainly responsible for the photobleaching of MR and the amino acids in these solutions by a mechanism involving O₂(¹∆g) generated probably by an excited state of the CT complex. MR generates O₂(¹∆g) with a relatively high yield (Φ ∆= 0.23 ± 0.04) and quenches O₂(¹∆g) only physically with = (2.3 ± 0.05) 108 M⁻¹ s⁻¹. This process does not affect the photosensitizing ability of MR under the low concentrations needed for its action. Non-donor compounds like the amino acid methionine and linoleic acid methyl ester are photodegraded by a Type II mechanism without implication of a dye CT complex.